Effectiveness of LPK Composite Flour as an Additive in the Formula of Enteral Diabetes Mellitus on Blood Glucose Levels of Type 2 Diabetes Mellitus Patients - Narda Widiada (Humanistic Network for Science and Technology (HNST), 2018)
Diabetes Mellitus (DM) is a group of metabolic diseases, more than 90-95% are Type 2 DM. Commercial enteral DM formulas such as diabetasol are quite expensive and there is a need for enteral DM formulas made from local foods that have the potential to be antihyglycemic and antidiabetic. Development of local food based enteral DM formulas with the addition of composite flour Labu Kuning, Kepok Banana and Green Beans (LPK). The food has a low glycemic index so that it can be used to control blood glucose levels in DM patients. The study was conducted to determine the effectiveness of LPK composite flour in the enteral DM formula for blood glucose levels in type 2 DM patients. Quasi experimental research, with a pre-post test with control group design. The treatment group was given FDM-LPK and the control group was given diabetasol, each 60 g per serving then measured blood glucose level 2 hours postprandial. Interventions are given for 5 consecutive days. The number of research subjects was 60 people consisting of 30 treatment people and 30 control people. Blood glucose in type 2 DM patients after 2 jpp in the treatment group and the control group showed a high average value (above 200 mg / dL). The treatment group ranged from 283.83 ± 103.62 mg / dL, while the control group ranged from 359.87 ± 134.43 mg / dL. On the second day there was a significant decrease in blood glucose levels (p 0.05). The provision of FDM-LPK by adding 85 g of LPK composite flour was effective to reduce blood glucose levels 2 jpp in type 2 DM patients. Reduction of blood glucose level of 2 jpp was 18.56%. Keywords: LPK composite flour, FDM-LPK, Diabetes mellitus, Blood glucose